Unveiling the Legal Impacts: The Unilateral Termination of the 1997 Russian-Ukrainian Friendship Treaty - Gunawan, Yordan; Riyanto, Aisyah Ajeng Putri; Farman, Logi (Jurnal Dinamika Hukum, 2024)
In 2022, Russian forces seized the capital of Ukraine, Kyiv, and reported more than 700 attacks on health facilities, personnel, and transport vehicles, resulting in the deaths of over 200 people. Despite encountering complex issues, Ukraine and Russia concluded the 1997 Russian-Ukrainian Friendship Treaty, which addressed matters of equality, sovereignty, and territorial integrity. However, Ukraine unilaterally terminated the Treaty in 2018. This research aims to analyze the legal implications arising from the unilateral termination of the Treaty, focusing on the realm of international law. The research employs a combination of normative legal research, analytical conceptual approaches, and case studies. The findings indicate that the termination of the Treaty adhered to Article 54(a) of the Vienna Convention on the Law of Treaties 1969. Nevertheless, the termination has resulted in legal uncertainty and has the potential to exacerbate pre-existing tensions, particularly regarding territorial integrity, which have intensified since 2014.